The Role of TPQ Muhajirin in Forming Children’s Religious Character in Bumi Ayu Village, Selebar District, Bengkulu City - Meli Septiana; Elisah Veby Alvitab; Riska Wulandari; Zia Komala Dewi; Alda Dwi Jayanti; Kurniawan (Yayasan Azhar Amanaa Yogyakarta, 2026)
Al-Qur’an Education Garden (TPQ) is one of the strategic community assets in shaping children’s religious character from an early age. This community service research was conducted at TPQ Muhajirin, Bumi Ayu Village, Selebar District, Bengkulu City, which holds great potential but requires strengthening in learning methods and activity management. The objective of this service program is to optimize the role of TPQ Muhajirin as a vehicle for forming children’s religious character through the Asset-Based Community Development (ABCD) approach. The method employed comprises four stages: Discovery (asset mapping), Dream (vision exploration), Design (program planning), and Destiny (implementation and sustainability). The program ran for 40 days from May 10 to June 20, 2026, with core activities scheduled every Monday and Tuesday, involving 10 KKN students from UIN Fatmawati Sukarno Bengkulu, 2 permanent teachers, and 30 active students. Results showed significant improvement in Qur’anic literacy skills (average +28.6%), prayer discipline (+26.7%), and noble moral character (+30.0%). The Societal Impact Index analysis from the satisfaction questionnaire indicated a community satisfaction level of 87.3%. This program provided measurable positive impact in strengthening children’s religious character education and serves as a local asset-based community service model that can be replicated in other regions.